Movement and Physical Activity in Early Childhood Education and Care Policies of Five Nordic Countries - Sollerhed, Ann-Christin; Olesen, Line Grønholt; Froberg, Karsten; Soini, Anne; Sääkslahti, Arja; Kristjánsdóttir, Gudrún; Vilhjálmsson, Rúnar; Fjørtoft, Ingunn; Larsen, Robert; Ekberg, Jan-Eric (MDPI AG, 2021)
The purpose of this study was to examine the values of movement and physical activity (MoPA) using government policy documents (e.g., laws and curricula) on early childhood education and care (ECEC) from Denmark, Finland, Iceland, Norway, and Sweden. This descriptive, comparative study was designed based on curriculum theory and used word count and content analyses to identify similarities and differences in the occurrence of MoPA in the ECEC policies of Nordic countries. Seven terms were identified as MoPA-related in Nordic policy documents. These terms occurred in various content contexts: development, environment, expression, health and well-being, learning and play, albeit sparsely. MoPA was referred to as both a goal in and of itself and as a means of achieving other goals (e.g., learning or development in another area). Formulations specifically dedicated to MoPA as a goal were present in the Danish and Finnish curricula and, to some extent, also in the Norwegian curriculum, while the Icelandic and Swedish curricula mentioned MoPA mostly as a means. Findings indicated that MoPA, which is important for children’s development, health, and well-being, is a low-priority value, to varying degrees, in the ECEC policies enacted by Nordic countries and the guidance provided to educators and stakeholders therein is inexplicit. peerReviewed